2020
DOI: 10.1101/2020.08.07.20170191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Review of AI and Data Science Support for Cancer Management

Abstract: Introduction - Thanks to improvement of care, cancer has become a chronic condition. But due to the toxicity of treatment, the importance of supporting the quality of life (QoL) of cancer patients increases. Monitoring and managing QoL relies on data collected by the patient in his/her home environment, its integration, and its analysis, which supports personalization of cancer management recommendations. We review the state-of-the-art of computerized systems that employ Data Science methods to monitor the hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 140 publications
(189 reference statements)
0
4
0
Order By: Relevance
“… 113 The most frequent interventions through APPs are to improve the quality of life of patients, to relieve adverse emotions, such as anxiety and depression, and to improve health status. 6 of these demonstrated 107 , 108 , 109 , 110 , 111 , 112 , 113 that interventions via the app were effective and of great value, while helping to improve clinical workflow and also removing barriers and limitations to access to specialty care. 1 of the studies of patients with colon cancer 113 indicated that the intervention via the app was not statistically significant versus the offline approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 113 The most frequent interventions through APPs are to improve the quality of life of patients, to relieve adverse emotions, such as anxiety and depression, and to improve health status. 6 of these demonstrated 107 , 108 , 109 , 110 , 111 , 112 , 113 that interventions via the app were effective and of great value, while helping to improve clinical workflow and also removing barriers and limitations to access to specialty care. 1 of the studies of patients with colon cancer 113 indicated that the intervention via the app was not statistically significant versus the offline approach.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies with interventions via APP alone. The populations included melanoma 110 , breast cancer 111 , lung cancer 112 , gynecologic tumors 113 , prostate cancer 114 , colon cancer 115 , and cancers J o u r n a l P r e -p r o o f that did not distinguish between disease types 116 . The most frequent interventions through APPs are to improve the quality of life (QoL) of patients, to relieve adverse emotions, such as anxiety and depression, and to improve health status.…”
Section: Digital Health Technologies (Dhts) Applied In Cancer Survivo...mentioning
confidence: 99%
“…151 While traditional screening methods have advanced research in the field, AI and ML can accurately monitor the health statuses of cancer patients, which can support the management of patients. 152 In particular, early detection of cancer through the adoption of AI and ML stands as one of the innovations of the 21st century that can significantly help control the prevalence of cancer globally. 153…”
Section: Discussionmentioning
confidence: 99%
“…151 While traditional screening methods have advanced research in the field, AI and ML can accurately monitor the health statuses of cancer patients, which can support the management of patients. 152 In particular, early detection of cancer through the adoption of AI and ML stands as one of the innovations of the 21st century that can significantly help control the prevalence of cancer globally. 153 The mapping and visualizing analysis of the keywords related to AI and ML in cancer research provides in-depth WordCloud analysis of the top 100 keywords based on the frequency, thematic analysis, structure, and development status of the topics found on similarities into five distinguish clusters, systematically and intuitively reveal the subject structure and development status and make predictions subject in the fields.…”
Section: Implications For Cancer Research and Controlmentioning
confidence: 99%